2019
DOI: 10.1021/acs.molpharmaceut.9b00703
|View full text |Cite
|
Sign up to set email alerts
|

Use of Terahertz-Raman Spectroscopy to Determine Solubility of the Crystalline Active Pharmaceutical Ingredient in Polymeric Matrices during Hot Melt Extrusion

Abstract: Polymer-based amorphous solid dispersions (ASDs) comprise one of the most promising formulation strategies devised to improve the oral bioavailability of poorly water-soluble drugs. Exploitation of such systems in marketed products has been limited because of poor understanding of physical stability. The internal disordered structure and increased free energy provide a thermodynamic driving force for phase separation and recrystallization, which can compromise therapeutic efficacy and limit product shelf life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…However, these do not predict the maximum solubility, or critical API concentration, in a given system. Such information would be useful, as the maximum solubility can vary for different API-polymer combinations (Bordos et al, 2019;Ekblad, 2018;Gupta et al, 2015;Solanki et al, 2018), resulting in different process-and product behaviour as reported in this study. The structured development program based on screening assays applied in this study, offered advantages over predictive models.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, these do not predict the maximum solubility, or critical API concentration, in a given system. Such information would be useful, as the maximum solubility can vary for different API-polymer combinations (Bordos et al, 2019;Ekblad, 2018;Gupta et al, 2015;Solanki et al, 2018), resulting in different process-and product behaviour as reported in this study. The structured development program based on screening assays applied in this study, offered advantages over predictive models.…”
Section: Discussionmentioning
confidence: 97%
“…Amorphous solid dispersions (ASD) exhibit higher internal energy than crystalline solid dispersions (CSD) (Zografi and Newman, 2017), which is seen as significant improvement of their aqueous solubility. However, this can also provide a thermodynamic driving force for phase separation and crystallisation (Bordos et al, 2019). This can give rise to stability studies of the amorphous formulations failing to meet product specification regarding their product performance.…”
Section: Introductionmentioning
confidence: 99%
“…The study discovered that the ASD of paracetamol has maximum stability when its concentration is 20 wt% in HPMC and 40 wt% in copovidone. The study showed that this novel spectroscopy combination can be used to provide real-time API-polymer phase equilibria and can be used to predict the stability of ASDs during the HME process (145).…”
Section: In-line Process Monitoring Tools To Improve Processing Parammentioning
confidence: 99%
“…Bordos et al proposed a novel approach of using an in-line terahertz (THz)-Raman Spectroscopy as a PAT to determine the saturation point of an API in a polymeric matrix during the HME process ( 145 ). The study carried out here uses paracetamol as a model API dispersed into two polymer systems, HPMC and copovidone.…”
Section: Recent Innovations In Hot-melt Extrusion To Prevent Thermal mentioning
confidence: 99%
“…For further formulation development, two polymeric matrices were selected with similar glass transition temperature, allowing us to combine both in the proposed mixture design: PVPVA and HPMC. These polymers show glass transition at 109 and 115 • C, respectively [36,37].…”
Section: Initial Trials and Extrusion Setupmentioning
confidence: 99%